Psychometric analysis of a KAP questionnaire on green dentistry using PLS-SEM and EFA: a pilot study - Nighat Zia; Jennifer Geraldine Doss; Mahmoud Danaee; Jacob John; Jeneen Panezai (BMC Oral Health)
Abstract Background Green dentistry promotes sustainable practices in oral healthcare. As environmental challenges intensify, integrating eco-friendly principles into dental education and practice becomes increasingly important. To advance sustainability in oral health settings, it is crucial to comprehend the knowledge, attitudes, and practices (KAP) of dental professionals and students. Despite growing interest, there is scarcity of research on green dentistry and a lack of standardized, validated tools to measure KAP makes it more difficult to compare studies. The rationale for this study was to conduct a psychometric analysis of a KAP questionnaire designed to assess eco-friendly clinical dental practices among dental school personnel and students in a dental school of Karachi. Method A 43-item questionnaire on green dentistry, adapted from existing green models and literature, and further validated through expert consultation and psychometric analysis, covers knowledge, attitudes, and practices. This cross-sectional pilot study involved 150 dental school personnel and students from the clinical side of an institution, using a self-administered, web-based questionnaire based on the Green Dental Model (GDM). The construct validity of ‘knowledge’ and ‘practice’ sections of the questionnaire was assessed using Partial Least Squares- Structural Equation Modeling (PLS-SEM) whereas Exploratory Factor Analysis (EFA) to uncover the latent factor structure of the ‘attitude’ section. Results Findings indicate that the model was identified as formative, with VIF values (< 5) indicating no multicollinearity. Through careful decision-making, almost all formative indicators were retained based on outer loads > 0.5. In EFA, factor loadings for the three extracted factors exceeded the reliability threshold. Factor 1 dealt with digital radiography and energy and water conservation; factor 2 involved waste management, recycling, and sterilization; and factor 3 represented green practices as a financial burden. Conclusion The instrument’s construct validity and feasibility makes it a valuable resource for sustainability focused researchers and dental professionals. This study uses advanced statistical techniques intended to address the questionnaire’s formative and reflective elements, improving the validity of assessment, a factor that was frequently overlooked in other studies on green dentistry. The distinctive contribution of this novel approach to the existing body of literature could facilitate potential research on the tool’s responsiveness to interventions on KAP change.